Strengthening Religious Moderation among Muslim Converts through Participatory Action Research: A Case Study in Aceh, Indonesia - Amin, Maimun Abdurrahman; Salman, Salman; Fualdi, Dede (Prodi Studi Agama-Agama, 2025)
Religious moderation is a vital foundation for maintaining social harmony in Aceh, particularly among Muslim converts who often struggle with religious and social adaptation. This study aims to describe how converts understand and practice moderation, to explore mentoring strategies carried out by the Aceh Da’wah Council (DDA) through a Participatory Action Research (PAR) approach, and to assess the changes in attitudes and social interactions that occurred during the program. The mentoring program was implemented over eight weeks (October–December 2024) with 35 participants, including DDA leaders and converts from different districts. Activities were organized into three stages: education and socialization, focus group discussions, and monitoring and evaluation. Data were collected through FGDs, semi-structured interviews, and participant observation, then analyzed qualitatively through data organization, coding, summarizing, and interpretation, with triangulation and member checking applied to strengthen credibility. The study found clear improvements in both the understanding and practice of religious moderation values. Converts demonstrated greater openness, respect for diversity, avoidance of extreme attitudes, and more active participation in community life. At the same time, the program reinforced the institutional role of the DDA, enhancing its capacity to provide sustained guidance for converts. The PAR approach proved relevant for fostering moderate religious attitudes among Muslim converts in Aceh by integrating Indonesia’s nine values of moderation into daily practice. While limited to the DDA setting, the study offers evidence that community-based mentoring can serve as a practical model for religious institutions and policymakers seeking to strengthen moderation and social harmony in comparable contexts.